Prisoners' Perception of Legitimacy of the Prison Staff: A Qualitative Study in Slovene Prisons - Hacin, Rok (International journal of offender therapy and comparative criminology, 2018)
The purpose of this article is to explore prisoners' perception of legitimacy of prison staff and examine the compliance of prisoners with the authority of prison staff to highlight the differences between instrumental and normative compliance of prisoners. This study draws on data collected from a random sample of 193 prisoners in all Slovene prisons. Using a qualitative approach based on structured interviews, our findings suggest that distributive justice, procedural justice, the quality of relations with prison staff, and the effectiveness of prison staff influence prisoners' perception of legitimacy in a prison environment. Several prisoners comply with prison rules because they fear sanctions, which indicates their instrumental compliance, while normative compliance was reported by prisoners who perceived the legitimacy of prison staff in a more positive manner. Overall findings indicate that both instrumental and normative compliance of prisoners can be observed in Slovene prisons.